Prisoner health - Levy, M.; Butler, Tony; Falconer, T. (Federation Press, 2005)
Any description of the health of prisoners needs to commence with the reiteration of the principle that a when a court of law sentences someone to imprisonment, "deprivation of liberty" should be the only punishment. Regrettably, in Australia at the turn of a new century, too many citizens are incarcerated because of hte consequences of illness.In reality, the "punishment" is only the beginning of a complex and punitive criminal justice system - prisoners, their families and their partners experience a number of "losses". There are levels of punishment - loss of privacy and loss of intimacy are just two that directly impact on the health of Australian prisoners. Regrettably, we confine our prisoners in conditions of physical squalor and overcrowding with the consequent health risks. Australian prisoners lose their Medicare entitlement. While this merely shifts the responsibility of primary health care onto the States and Territories, it significantly reduces the option of "second opinions" that the prisoner may request (as this now needs to be paid for by the prisoner or their family). These health risks and consequent health outcomes are readily transferred from the prison environment back to the outside community.